QUANTITATIVE ANALYSIS OF PRODUCTION THEORY CAPOEITA IN THE ANNALS OF FIEP AND CONBRACE (Fiep Bulletin - online, 2013)
The objective of this article is to identify the volume of production theory, related to Capoeira matter, present in the annals of the Federation International d 'Education Physique (FIEP) and the Brazilian Congress of Science of Sports (CONBRACE), to identify the issues for which the Capoeira is being addressed and that may well serve as a database for future work on Capoeira. After the mapping of these proceedings, make categories in which the publications were entered and analyzed. It was concluded that Capoeira is still a subject little discussed in academic, and that the subject in which it is most discussed is related to the category of teaching-learning on Capoeira.
Keywords: capoeira; theoretical production; categories